2018
DOI: 10.1002/asia.201701795
|View full text |Cite
|
Sign up to set email alerts
|

Motion‐Induced Changes in Emission as an Effective Strategy for the Ratiometric Probing of Human Serum Albumin and Trypsin in Biological Fluids

Abstract: Herein, we report the formation of a highly luminescent, pH-sensitive, thermoreversible nanoaggregate in pure aqueous medium through the self-agglomeration of carbazole-based amphiphiles. The self-assembly process restricted the intramolecular motion of the molecules and induced a change in its emission signal from blue to cyan, owing to an aggregation-induced emission (AIE) effect. A similar type of ratiometric response was also observed in the presence of human serum albumin (HSA). However, in this case, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 36 publications
(24 citation statements)
references
References 73 publications
0
24
0
Order By: Relevance
“…On the contrary, the FT-IR spectrum of SLNPV reveals that the stretching frequencies related to the α-helix conformation (amide I band) were found to be affected by the interaction with 1 (Figure S4a). 34 Thus, we can speculate that the charge pairing between 1 and SLNPV might partially modify the 3D structure of the polyhedral protein. Additionally, we have characterized the interaction of compound 1 with SLNPV via circular dichroism (Figure S4b).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…On the contrary, the FT-IR spectrum of SLNPV reveals that the stretching frequencies related to the α-helix conformation (amide I band) were found to be affected by the interaction with 1 (Figure S4a). 34 Thus, we can speculate that the charge pairing between 1 and SLNPV might partially modify the 3D structure of the polyhedral protein. Additionally, we have characterized the interaction of compound 1 with SLNPV via circular dichroism (Figure S4b).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…The selectivity investigation of compound 1 in the presence of various biologically ionic analytes, neutral compounds, and thiol-containing amino acids showed that only HSA induced an increase in fluorescent emission. 21 In 2019, Tu et al designed a series of specific and quantitative tetrazolate-functionalized AIEgens for albumin detection, namely TPE-4TA, (Z)-TPE-2TA, and (E)-TPE-2TA. Fluorescence assay showed that the minimum detectable HSA concentration was in the range of 0.21-0.31 nM.…”
Section: Albuminmentioning
confidence: 99%
“…It can also serve as a biomarker for many diseases, such as cardiovascular and neurodegenerative diseases. 21 Zhao et al designed fluorescent strips of electrospun fibers for detecting trypsin in urine. Their PSMA-PhB + TPE/Pro strip could provide ratiometric color change when urine trypsin presented.…”
Section: Othersmentioning
confidence: 99%
See 1 more Smart Citation
“…As a continuation of our on‐going endeavor in the field of molecular sensor, herein we have designed an p ‐phenylenevinylene based optical probe with multiple interaction sites (Figure ). Incorporation of ‘mutually exclusive’ responsive units in the same molecule enable us to develop a ‘smart probe’ which can selectively detection of both these metal ions (Cu 2+ and Zn 2+ ) and fluoride simultaneously using incongruous sensing pathways.…”
Section: Introductionmentioning
confidence: 99%